FOXP2 variants in 14 individuals with developmental speech and language disorders broaden the mutational and clinical spectrum. Issue 1 (29th August 2016) - Reuter, Miriam S; Riess, Angelika; Moog, Ute; Briggs, Tracy A; Chandler, Kate E; Rauch, Anita; Stampfer, Miriam; Steindl, Katharina; Gläser, Dieter; Joset, Pascal; ,; Krumbiegel, Mandy; et al.
Abstract : Background: Disruptions of the FOXP2 gene, encoding a forkhead transcription factor, are the first known monogenic cause of a speech and language disorder. So far, mainly chromosomal rearrangements such as translocations or larger deletions affecting FOXP2 have been reported. Intragenic deletions or convincingly pathogenic point mutations in FOXP2 have up to date only been reported in three families. We thus aimed at a further characterisation of the mutational and clinical spectrum. Methods: Chromosomal microarray testing, trio exome sequencing, multigene panel sequencing and targeted sequencing of FOXP2 were performed in individuals with variable developmental disorders, and speech and language deficits. Results: We identified four different truncating mutations, two novel missense mutations within the forkhead domain and an intragenic deletion in FOXP2 in 14 individuals from eight unrelated families. Mutations occurred de novo in four families and were inherited from an affected parent in the other four. All index patients presented with various manifestations of language and speech impairment. Apart from two individuals with normal onset of speech, age of first words was between 4 and 7 years. Articulation difficulties such as slurred speech, dyspraxia, stuttering and poor pronunciation were frequently noted. Motor development was normal or only mildly delayed. Mild cognitive impairment was reported for most individuals. Conclusions: By identifying intragenic deletions or mutations in 14 individuals from eight unrelated families with variable developmental delay/cognitive impairment and speech and language deficits, we considerably broaden the mutational and clinical spectrum associated with aberrations in FOXP2 .